Empirical relationships for remote sensing reflectance and Noctiluca scintillans cell density in the northeastern Arabian Sea. (December 2020) - Pandi, Sudarsana Rao; Baliarsingh, Sanjiba Kumar; Lotliker, Aneesh Anandrao; Sarma, Nittala S.; Tripathy, Sarat Chandra
Abstract: A dinoflagellate under the ambit of Harmful Algal Blooms (HAB), the bioluminescent Noctiluca scintillans ( NS ), has been infesting the northern Arabian Sea increasingly over the last few decades during late winter. Their occurrence is found to be due to seasonal oscillations in the coastal currents. The physical and biogeochemical parameters associated with the seasonal blooms are reasonably well known. But accurate quantitative estimation capability using remote sensing sensors over the extensive oceanic regime is still lacking. This is especially due to a lack of information on bio-optical properties associated with cell density measurements. We attempted to show that remote sensing reflectance and chl- a show significant relationship e.g., Rrs (531)/Rrs (510) = 0.8261 + 6.06 × 10 −6 NS + 0.02323chl- a ( N = 19, R 2 adj = 0.99, p = 2.5 × 10 −17, RMSE = 0.1083) which is applicable over diverse areas of the northeastern Arabian Sea e.g., coastal, shelf and offshore regions. The model is supported by a second dataset with an RMSE of 0.022893 ( N = 8) for the Rrs (531)/Rrs (510) ratio. The NS cell densities were derived from the Rrs(510)/Rrs(531) band ratio within reasonable error and accuracy limits. Including sensor capability at 510 nm is suggested in future satellite launches. Highlights: Late winter bloom of Noctiluca scintillans ( NS ) captured in the NEAS Coupled time-series study of NS cell counts and in situ light field Rrs(531)/Rrs(510) band ratio modelled versus cell density and chl-a NS cell density is predicted from Rrs(510)/Rrs(531) band ratio. Including 510 nm channel in future satellite launches suggested